Personalizacja jako wyzwanie rozwojowe dorosłości – wokół problemu autokreacyjnych możliwości podmiotu - Kuryś-Szyncel, Karolina (Wydawnictwo Naukowe UAM, 2013)
The article refers to personalization patterns which stimulate development in adulthood. These are: confrontation with the circumstances of life, implementation of life’s tasks, seeking and adapting patterns of personal self-creation. The author notes that each of these mechanisms can be seen and experienced as a conflict. Particular attention is paid to the pattern of self-creation, subjected to empirical verification. The text analyses personal stories provoked by the narrative impulse: “Who is this I?” The analysis helps reconstruct the three orientations of the narrative and indicates the characteristics of the wholeness type of personality.
Personalization as a Developmental Challenge of Adulthood – Around the Question of Personal Self-creation Possibilities
Keywords: personalization; self-creation; development in adulthood; narrative